A Case of Valproate Induced Hyperammonemic Encephalopathy. (4th May 2011) - Tarafdar, Surjit; Slee, Mark; Ameer, Faisal; Doogue, Matt
Abstract : A 36-years-old man on phenytoin, levetiracetam, and sodium valproate presented with acute confusion. Routine investigations including serum valproate and phenytoin concentration were normal. His serum ammonia concentration was raised. His valproate was held and 2 days later he recovered with concordant normalisation of serum ammonia concentration. Urea acid cycle disorder was ruled out, and a diagnosis of valproate induced hyperammonemic encephalopathy (VHE) was made. Asymptomatic hyperammonemia occurs in 15–50% of valproate-treated patients, and while the true incidence of VHE is not known, it is a recognized complication of sodium valproate treatment. VHE typically presents acutely with impaired consciousness, lethargy, and vomiting. Valproate concentrations may be in the therapeutic range, and liver function tests are typically "normal." Treatment for VHE consists of ceasing valproate and providing supportive care. Some have advocated carnitine replacement.